Juridical Study of The Implementation of The Principles of Equality of The Parents Parties In Contruction Action Contract Which Is Made In A Notary Face - Nasution, Adli Dzil; Suprayitno, Suprayitno; Mansar, Adi (Veteran Law Review, 2021)
The principle of equality, contact, notar The juridical concept of the principle of equality in the perspective of contract law is based on a civil law system that conforms to the values of justice. Contracts based on a civil law system that are in accordance with the values of justice, actually in Indonesia the application of the principle of freedom of contract is not absolute, there are certain limitations regulated in the Civil Code and other laws and regulations. The restrictions on freedom of contract that are regulated in the Civil Code include that there are no defects in the agreement, namely coercion, error, and fraud. The form of the principle of equality of the parties in the construction work contract deed made before a Notary, regarding the authority of the notary in making contracts, in Article 15 of Law Number 2 of 2014 concerning amendments to Law Number 30 of 2004 concerning the Position of a Notary, is a public official those who are authorized to make both authentic deeds and under-hand deeds as long as they are not specific to other public officials in accordance with statutory regulations or the wishes of the parties concerned to ensure that the rights and obligations of the parties are guaranteed and have legal certainty